Calculating evidence-based renal replacement therapy – Introducing an excel-based calculator to improve prescribing and delivery in renal replacement therapy – A before and after study. (February 2016) - Cottle, Daniel; Mousdale, Stephen; Waqar-Uddin, Haroon; Tully, Redmond; Taylor, Benjamin
Background: Transferring the theoretical aspect of continuous renal replacement therapy to the bedside and delivering a given "dose" can be difficult. In research, the "dose" of renal replacement therapy is given as effluent flow rate in ml kg −1 h −1 . Unfortunately, most machines require other information when they are initiating therapy, including blood flow rate, pre-blood pump flow rate, dialysate flow rate, etc. This can lead to confusion, resulting in patients receiving inappropriate doses of renal replacement therapy. Our aim was to design an excel calculator which would personalise patient's treatment, deliver an effective, evidence-based dose of renal replacement therapy without large variations in practice and prolong filter life. Our calculator prescribes a haemodialfiltration dose of 25 ml kg −1 h −1 whilst limiting the filtration fraction to 15%. Methods: We compared the episodes of renal replacement therapy received by a historical group of patients, by retrieving their data stored on the haemofiltration machines, to a group where the calculator was used. In the second group, the data were gathered prospectively. Results: The median delivered dose reduced from 41.0 ml kg −1 h −1 to 26.8 ml kg −1 h −1 with reduced variability that was significantly closer to the aim of 25 ml kg −1 .h −1 ( p < 0.0001). The median treatment time increased from 8.5 h to 22.2 h ( p = 0.00001). Conclusion: Our calculator significantly reduces variation in prescriptions of continuous veno-venous haemodiafiltration and provides an evidence-based dose. It is easy to use and provides personal care for patients whilst optimizing continuous veno-venous haemodiafiltration delivery and treatment times.